Association of 8q24.21 locus with the risk of colorectal cancer: A systematic review and meta-analysis - Haerian, M.S.; Haerian, B.S. (Lippincott, Williams & Wilkins, 2011)
Objective: Recent genome-wide association studies of colorectal cancer (CRC) have identified rs6983267 G>T and rs10505477 T>C polymorphisms as key loci in the 8q24 region to be associated with CRC. In the present study, we performed a meta-analysis to determine whether these loci are risk factors for susceptibility to CRC. Materials and Methods: We meta-analyzed the 22 included studies (47,003 cases and 45,754 controls) that evaluated the role of rs6983267 G>T and rs10505477 T>C polymorphisms with CRC risk under alternative genetic models. Results: Meta-analysis of the pooled data showed allelic and genotypic association of the rs6983267 polymorphism with CRC risk in the Asian, European, and Americans with European ancestry. Sub-analysis of the American studies showed negative results in the studies with non-identified ethnicity of the subjects. Meta-analysis of included studies of rs10505477 polymorphism identified allelic and genotypic association with CRC risk in the American subjects. Further meta-analysis of the American studies demonstrated positive results in the studies with non-identified ethnicity of the samples. Conclusion: Our data suggested that the rs6983267 G>T polymorphism is a risk factor for CRC in the Asians, European, and American with the European ancestry populations.